Smart Augmented Learning - et. al., Shanthini.E , (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Education is the foundation of our society. The most important investment we can make collectively and individually is in education. Rural education is of utmost importance to enhance and develop the livelihood of rural people indirectly. But the face of education in rural parts of the country has to be considered for a serious check-up with children failing to receive a good quality of education. This is one of the reasons to drivestudents away from attending their schools. The education system in rural areas is information based rather than a practical oriented, which is a major setback for the economic growth of the nation. The prominent crises that hold back rural schools are the lack of smart learning technology and no proper access to laboratory equipment for the students. Augmented Reality (AR) is one of the finest technologies that can be utilized for education development as it amplifies the learning process.Marker-based AR android application can help by over-laying audio-visuals, computer graphics, 3-D graphical models’ representation, the contextual information of concept’s procedures, processes, working, functions and its usage directly over the manuals which make the subject more understandable and comprehensive, thus enhances the student’s knowledge. The utilization of AR technology in the field of education will prove to be a great positive societal impact essentially for rural school students. It sets a path for learning all the concepts smartly and efficiently. AR-based learning can create an impact because there is no need for the internet. The mobile application also helps to improve the student’s self-learning skills. In this paper, some concepts from biology and physics are considered, the graphical models, functionality and working are displayed in AR with the help of Maya 3D, Unity 3D.